Early Detection and Investigation of Extracellular Vesicles Biomarkers in Breast Cancer - Bandini, Erika; Rossi, Tania; Scarpi, Emanuela; Gallerani, Giulia; Vannini, Ivan; Salvi, Samanta; Azzali, Irene; Melloni, Mattia; Salucci, Sara; Battistelli, Michela; Serra, Patrizia; Maltoni, Roberta; et al. (Frontiers in Molecular Biosciences, 2021)
Breast cancer (BC) is the most commonly diagnosed malignant tumor in women worldwide, and the leading cause of cancer death in the female population. The percentage of patients experiencing poor prognosis along with the risk of developing metastasis remains high, also affecting the resistance to current main therapies. Cancer progression and metastatic development are no longer due entirely to their intrinsic characteristics, but also regulated by signals derived from cells of the tumor microenvironment. Extracellular vesicles (EVs) packed with DNA, RNA, and proteins, are the most attractive targets for both diagnostic and therapeutic applications, and represent a decisive challenge as liquid biopsy-based markers. Here we performed a study based on a multiplexed phenotyping flow cytometric approach to characterize BC-derived EVs from BC patients and cell lines, through the detection of multiple antigens. Our data reveal the expression of EVs-related biomarkers derived from BC patient plasma and cell line supernatants, suggesting that EVs could be exploited for characterizing and monitoring disease progression.